Role of systematic pelvic and para‐aortic lymphadenectomy in delayed debulking surgery after six neoadjuvant chemotherapy cycles for high‐grade serous ovarian carcinoma. Issue 8 (16th May 2021) - Lopes, Andre; Genta, Maria L. N. D.; da Costa Miranda, Vanessa; Aranha, Andrea; Lopez, Rossana V. M.; Piato, Dariane S. A. M.; Anton, Cristina; Carvalho, Filomena M.; del Pilar Esteves Diz, Maria; Carvalho, Jesus P.
Abstract: Introduction: We analyzed the role of systematic pelvic and para‐aortic lymphadenectomy in delayed debulking surgery after six neoadjuvant chemotherapy (NACT) cycles for advanced high‐grade serous ovarian carcinoma. Materials and Methods: We retrospectively reviewed patients with advanced ovarian carcinoma who underwent NACT with carboplatin‐paclitaxel between 2008 and 2016. Patients were included only if they had FIGO IIIC‐IVB high‐grade serous carcinoma with clinically negative lymph nodes after six NACT cycles (carboplatin‐paclitaxel) and underwent complete or near complete cytoreduction. Patients with partial lymphadenectomy or bulky nodes were excluded. Patients who underwent systematic pelvic and aortic lymphadenectomy and those who did not undergo lymph node dissection were compared. Progression‐free and overall survivals were analyzed using the Kaplan–Meier method. Results: Totally, 132 patients with FIGO IIIC‐IVB epithelial ovarian carcinoma were surgically treated after NACT. Sixty patients were included (39 and 21 in the lymphadenectomy and nonlymphadenectomy group, respectively); 40% had suspicious lymph nodes before NACT. Patient characteristics, blood transfusion numbers, and complication incidence were similar between the groups. In the lymphadenectomy group, 12 patients (30.8%) had histologically positive lymph nodes and the surgical time was longer (229 vs. 164 min). The median overall survival in the lymphadenectomy and nonlymphadenectomy groups, respectively, was 56.7 (95% CI 43.4–70.1) and 61.2 (21.4–101.0) months ( p = 0.934); the corresponding disease‐free survival was 8.1 (6.2–10.1) and 8.3 (5.1–11.6) months ( p = 0.878). Six patients exclusively presented with lymph node recurrence. Conclusions: Systematic lymphadenectomy after six NACT cycles may have no influence on survival.